Effect of orthostatic hypotension on long-term prognosis of elderly patients with stable coronary artery disease: a retrospective cohort study - Hu, Jiaman; Chi, Jianing; Cai, Hua; Wu, Ningxia; Li, Pengfei; Huang, Yuekang; Lin, Cailong; Lai, Yingying; Huang, Jianyu; Li, Weihua; Su, Peng; Li, Min; et al. (Frontiers in Cardiovascular Medicine, 2024)
The long-term prognosis of patients with stable coronary artery disease (CAD) combined with orthostatic hypotension (OH) was rarely reported. This research was designed to examine whether OH increases the risk of all-cause mortality and cardiovascular death among patients with stable CAD.We retrospectively analyzed retired militaries over 65 years old who were hospitalized at the General Hospital of Southern Theater Command between March and July 2010. There were patients with stable CAD included, among whom 263 had OH. The risk of all-cause mortality and cardiovascular death in OH and non-OH groups were analyzed with Cox proportional risk models, and restricted cubic spline plots were utilised for subgroup analyses. Furthermore, competing risk models were applied for sensitivity analyses.The median age of the patients was 82.00 [80.00, 85.00] years. Over 159 months of followup, the loss to follow-up rate was 2.27%, and all-cause mortality was observed in 574 (63.57%) patients, including 184 with OH. Moreover, cardiovascular death occurred in 127 patients (13.73%), with 58 cases associated with OH. Although the relationship between OH and all-cause mortality was nonsignificant (BMI<25 group, adjusted hazard ratio [HR]=1.10 with a 95% confidence interval [CI]: 0.82-1.40; BMI ≥25 group, adjusted HR = 1.30, 95% CI: 0.98-1.70), it was independently related to a growing risk of cardiovascular death (adjusted HR = 1.80, 95% CI: 1.20-2.60). This finding was further validated by using a competing risk model (subdistribution hazard ratio [sHR] = 1.74, 95% CI:1.22-2.49). What's more, the age, low-density cholesterol, and frequency of hospital admissions were identified as risk factors of cardiovascular death among patients with OH (p<0.05).Our study-based retired militaries with stable CAD found that OH led to a significantly higher risk of cardiovascular death, but the OH was not noticeably associated with all-cause mortality on long-term prognosis.